Awareness and understanding of the threats for the health of the behavioral risk factors in the development of non-communicable diseases by the young people as an important component of the implementation of preventive measures (Environment & Health, 2018)
Background: The topicality is stipulated by the necessity for the study both the level of the awareness of young people regarding risk factors of the development of non-communicable diseases and the level of their prevalence for the prediction of the consequences of the implementation of preventive measures.Objective: We determined the level of the awareness of the students about behavioral risk factors for the development of non-communicable diseases and understanding of the threats of these factors by them.Materials and methods: We performed the questionary in the students (430 respondents) of the Kyiv National Trade and Economic University in the speciality: food technology and commodity science about main risk factors for the development of non-communicable diseases and understanding of the role of the lifestyle for the health preservation in the young people.Results: The majority of the students was shown to be aware of the influence of the behavioral factors on the development of non-communicable diseases, the effect of inefficient nutrition - 87.4%, insufficient physical activity - 80.9%, alcohol and low-alcohol beverages - 92.2%, smoking - 91.6%. However, this awareness does not lead to understanding of the threat for their health: they consume sweet fizzy and low-alcohol beverages (girls - 68%, boys - 92%, girls - 65%, boys - 71% , respectively), every third girl and over 40% prefer to drink tea or coffee with 2 or more spoons of sugar, use 25 grams and more salt daily, and 25% of the respondents consume margarines and spreads, about 25% do not consume fruits and vegetables every day, 23.8% of the girls, 43.7% of the boys, and 10.3% of the respondents smoke cigarettes and use drugs.Only 55% of the respondents were estimated to point to an active lifestyle and maintaining of their physical form.The study indicates the need for the further improvement of the information and training programs to improve the awareness and understanding of the dangers of the main behavioral risk factors for the development of non-communicable diseases by the young people.
Keywords: non-communicable diseases; behavioral risk factors; lifestyle; awareness; understanding; questionnaires